Road Worriors (Frontlines of construction)
Whether its Indy race cars ripping at speeds of 350 kilometres an hour or weekend warriors rushing to get to cottage country, drivers are constantly competing for dominance and speed. Road Warriors takes us to the road to meet racers, road builders, and speedways where good driving and good engineering are the difference between life and death.